Performance evaluation of an on-site biocomplex textile as an alternative daily cover in a sanitary landfill, South Korea. Issue 12 (December 2018) - Yun, Jeonghee; Jung, Hyekyeng; Choi, Hyungjoo; Oh, Kyung-Cheol; Jeon, Jun-Min; Ryu, Hee Wook; Cho, Kyung-Suk
The performance of a biocomplex textile prototype was evaluated as an alternative daily cover at an operational landfill site to mitigate odors and methane. The biocomplex textile prototype consisted of two layers of nonwoven fabric and biocarrier immobilized microorganisms and showed excellent removal of odors and methane compared to landfill cover soil. The complex odor intensity (odor dilution ratio (ODR)) on the surface of landfill cover soil was 1, 000–10, 000 ODR (average of 4, 204 ODR), whereas it was 5–250 ODR (average of 55 ODR) on the surface of biocomplex textile. Hydrogen sulfide, which contributes a significant odor intensity, had an average concentration on the biocomplex textile of 8.64 parts-per-billion (ppb), compared to 1733.21 ppb on the landfill cover soil. The biocomplex textile also showed effective methane removal with methane concentrations of 0–1.2% (average of 0.3%) on the biocomplex textile compared to 0–20% (average of 5.3%) on the landfill cover soil. Bacterial community diversity in the biocomplex textile increased with time until an operating period of 66 days, after which diversity indices were maintained at a constant level. The dominant species were the methanotrophs Methylocaldum and Methylobacter, and the non-methanotrophs Acinetobacter, Serpens, Ohtaekwangia, and Actinophytocola . These results demonstrate that on-site biocomplex textile is a suitable alternative daily cover to mitigate odors and methane in landfills.